The Corporate Liability as Perpetrator of Environmental Pollution Crime - Putra, Panca Sarjana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Corporations grow and develop according to the times, the principle of corporations with the smallest capital to get the maximum profit, making corporations can do anything to gain profits. Corporations are required to run their business in good faith, corporations that do not run their business in good faith can be held criminally liable. The increasing number of corporations as a global impact creates a special concern for environmental impacts. Almost every field of business, whether in mining, trade, industry, natural resource utilization and others, has the potential to cause pollution and damage to the environment. The opposition to the discourse of holding corporations accountable in criminal law has always been justified. The argument is also inseparable from the natural flows of criminal law, both the classical flow (daad strafrecht), the modern flow (dader strafrecht) and the neoclassical flow (daad-dader strafrecht) which only sees individuals as perpetrators or legal subjects. It is not necessary to prove the guilt committed by the Corporation in carrying out its business activities of using, producing, managing hazardous and toxic waste (B3), which as a result of the act poses a serious threat to environmental damage is a positive progress towards the development of criminal law politics in Indonesia. This research is normative juridical in the form of analysis regarding legal norms both international conventions and provisions of Indonesian positive law that regulate corporate liability as perpetrators of environmental pollution crimes. With the formulation of the problem, how is the regulation of environmental management crimes that can be committed by corporations and how is the criminal liability of corporations as perpetrators of environmental pollution crimes. The conclusion show that the Criminal Code (KUHP) only recognizes individuals as subjects of criminal law, while corporations have not been considered as subjects of criminal law.